간호대학생의 진로결정수준과 진로준비행동의 관계에서 셀프리더십의 매개효과 - 문미경; Mikyung Moon; 김소연; Soyeon Kim (보건정보통계학회지, 2017)
Objectives: The purpose of this study was to investigate the mediating effect of self-leadership on the relationship between career decision level and career preparation behavior of nursing students. Methods: The subjects were 179 nursing college students using questionnaires with a total of 63 items including general characteristics (11 items), career decision level (18 items), career preparation (16 items), and self-leadership (18 items) respectively. The collected data were analyzed by SPSS Statistics 23 using the mean, standard deviation, t-test, ANOVA (Scheffe test), Pearson`s correlation coefficient, multiple regression analysis and Sobel test. Results: The mean score of career decision level was 2.79±0.45, career preparation behavior was 2.59±0.48, and self-leadership was 3.75±0.45. Career preparation behaviors were positively correlated with career decision level (r=0.40, p<0.001) and self-leadership (r=0.32, p<0.001). The level of career decision was positively correlated with self-leadership (r=0.28, p<0.001). The higher the career decision level and the self-leadership, the better the career preparation behavior. The higher the self-leadership, the higher the career decision level. Sobel test showed that the mediating effect of self-leadership was significant (z=2.32, p<0.001). Conclusions: A variety of educational programs should be attempted in various ways to improve self-leadership in order to drive career preparedness.